On the Nonmonotonic, Hormetic Photoprotective Response of Plants to Stress. Issue 2 (13th April 2019) - Agathokleous, Evgenios; Kitao, Mitsutoshi; Harayama, Hisanori
Accumulated evidence show that reactive species play a dual role in plants as well, with likely biphasic responses. This suggests that photoprotective mechanisms may also show similar patterns because they are highly related to reactive species. The nonphotochemical quenching (NPQ) is an index of heat dissipation of excitation energy in the antenna system. We present here preliminary evidence from some published studies showing significant biphasic response of NPQ to increasing doses of stress, with U-shaped or inverted U-shaped dose–response relationships, typical of hormesis. This evidence provides a remarkable perspective for designing novel studies where the fate of light energy will be seen through the lens of hormesis.